DIGITAL MARKETING WITH LANDING PAGE TO IMPROVES SELLING OF MSMES DECHEFDEFINZS - Rr. Artiana Krestianti; Raldy Hendrianu; Rooswhan Budhi Utomo; Ali Akbar; Lely Prananingrum (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Micro, small and medium enterprises (MSMEs), which are the main supporting of the Indonesian economy, need attention, because they can absorb labor and reduce the cost of unemployment by competing for jobs in the formal sector. This research aims  is to assist MSMEs Dechefdefinzs in marketing their products to prospective customers. The landing page method uses the waterfall methodology, by collecting data, analyzing data, making designs from an analyzed data, making coding, and testing the landing page and website. Developing this web-based application uses the HTML and PHP programming language with the Laravel framework which easy to apply at this time and in the long run. Creating a Dechefdefinzs landing page and website hopefuly can expand and spread widely its products in the society, such as traditional cakes, cake pans, bakery, rice menus and cookies. This website also makes it easier for customers to orders and get product information just by looking at the website without having to come to the location. Keywords: landing page, MSMEs, waterfall, website. Abstrak: Usaha mikro, kecil dan menengah (UMKM) yang merupakan penopang utama perekonomian Indonesia perlu mendapat perhatian, karena mereka dapat menyerap tenaga kerja dan mengurangi biaya pengangguran dengan bersaing mendapatkan pekerjaan di sektor formal. Penelitian ini bertujuan untuk membantu UMKM Dechefdefinzs dalam memasarkan produknya kepada calon konsumen. Metode yang digunaakan dalam pembuatan landing page  dan website  adalah metode waterall, dengan cara pengumpulan data, analisis data, pembuatan desain dari data yang dianalisis, pembuatan program, dan pengujian terhadap landing page dan website. Pengembangan aplikasi berbasis web ini menggunakan bahasa pemrograman HTML dan PHP dengan framework Laravel yang mudah diterapkan saat ini dan jangka panjang. Dengan dibuatnya landing page dan website Dechefdefinzs diharapkan dapat memperluas dan menyebarkan produk-produknya secara luas di masyarakat, seperti kue tradisional, kue loyang, roti, menu nasi dan kue kering. Website ini juga memudahkan pelanggan dalam memesan dan mendapatkan informasi produk hanya dengan melihat website tanpa harus datang ke lokasi. Kata kunci: landing page, UMKM, waterfall, website.